Liver cancer: WISP3 suppresses hepatocellular carcinoma progression by negative regulation of β‐catenin/TCF/LEF signalling. (22nd February 2019) - Gao, Hong; Yin, Fen‐Fen; Guan, Dong‐Xian; Feng, Yu‐Xiong; Zheng, Qian‐Wen; Wang, Xiang; Zhu, Min; Zhang, Xue‐Li; Cheng, Shu‐Qun; Chen, Tian‐Wei; Jiang, Hao; Zhang, Er‐Bin; et al.
Abstract: Objectives: Wnt1‐inducible signalling pathway protein 3 (WISP3/CCN6) belongs to the CCN (CYR61/CTGF/NOV) family of proteins, dysregulation of this family contributed to the tumorigenicity of various tumours. In this study, we need to explore its role in hepatocellular carcinoma that remains largely elusive. Materials and Methods: The expression of WISP3/CCN6 was analysed by qRT‐PCR and Western blotting. Effects of WISP3 on proliferation and metastasis of HCC cells were examined, respectively, by MTT assay and Boyden Chamber. Roles of WISP3 on HCC tumour growth and metastatic ability in vivo were detected in nude mice. Related mechanism study was confirmed by immunofluorescence and Western blotting. Results: The expression of WISP3 was significantly downregulated in HCC clinical samples and cell lines, and reversely correlated with the tumour size. Forced expression of WISP3 in HCC cells significantly suppressed cell growth and migration in vitro as well as tumour growth and metastatic seeding in vivo. In contrast, downregulation of WISP3 accelerated cell proliferation and migration, and promoted in vivo metastasis. Further study revealed that WISP3 inhibited the translocation of β‐catenin to the nucleus by activating glycogen synthase kinase‐3β (GSK3β). Moreover, constitutively active β‐catenin blocked the suppressive effects of WISP3 on HCC. Conclusions: Our study showed that WISP3 suppressed the progression of HCC by negative regulation of β‐catenin/TCF/LEF signalling, providing WISP3 as a potential therapeutic candidate for HCC.